Lean Knowledge Management in The Adoption of Traceability Technology For Halal Perishable Food Supply Chain: a Systematic Literature Review - Wresni Anggraini; Wakhid Slamet Ciptono; Luluk Lusiantoro; Heru Kurnianto Tjahjono (Yayasan Riset dan Pengembangan Intelektual (YRPI), 2024)
This research was perfomed to provide a comprehensive Systematic Literature Review (SLR) on the mutually beneficial link between Lean and Knowledge Management (LKM). The primary focus was to highlight the crucial role of LKM as an enabler in empowering perishable food supply chains (PFSC) to effectively embrace traceability technology, ensuring the integrity of halal supply chains. The research was carried out using the SLR method and adhered to the procedures of the Preferred Reporting for Systematic Reviews and Meta-Analyses (PRISMA). In total, 65 articles from the Scopus database, published in various journals over 22 years were chosen, mapped, and evaluated. Furthermore, there were several featured forms of mutual collaboration between Lean and Knowledge Management (KM). The implementation of LKM in halal supply chain traceability for perishable food was still absent from the literature. Efficient (lean) KM processes for business actors turned knowledge into added value for the PFSC. The vital role of LKM as an enabler for PFSC in adopting traceability technology, which is characterized as fast-changing technology and highly knowledge-centric, is by eliminating wasteful knowledge so could advance responsiveness, efficiency, and flexibility. Considering the important role of LKM as an enabler of PFSC to address complex challenges in traceability technology adoption, collaborative interdisciplinary research is needed. Academic publications exploring the incorporation of lean and KM in the context of PFSC were relatively scarce. This SLR represented one of the pioneering efforts to investigate the amalgamation and its potential to overcome obstacles and inhibitors in the adoption of traceability technology.